Green Tea Extract’s Hepatoprotective Properties against Cyclophosphamide-Induced Liver Damage - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Consuming green tea has been linked to a decreased risk of cancer, cardiovascular disease, and neurological diseases. For this reason, green tea extract has been added to diets along with other multivitamins and supplements. Aim of the Work: investigating the impact of cyclophosphamide (CP) on male albino rat livers and the potential protective function of green tea extract. Materials and Methods: Twenty-four adult male albino rats were used in the current study. Three equal groups were formed out of them, each with eight rats. For 9 weeks, Group I (the control group) received I. P. (intraperitoneal) injections of normal saline at a dosage of 0.5 mg/kg body weight twice a week. Group II received 2 weeks of intraperitoneal injections of CP at a dose of 150 mg/kg/day. Group III: For 2 weeks, rats received intraperitoneal injections of 150 mg/kg/day of CP in addition to 3 weeks of oral green tea extracts (50 mg/kg/day). Results: The livers of rats given CP exhibited a number of histological and histochemical alterations. Green tea was used to ameliorate these modifications. Conclusion: The current study demonstrated the preventative and curative effects of green tea on albino rats’ livers following CP exposure.